Effect of Moisture Content on the Shear Behaviour of a Completely Decomposed Granite: An Experimental Study - Pan Liu; Jinhong Lin; Yang Wang; Xueqiang Yang (Advances in Civil Engineering)
To figure out the effect of moisture content on the shear behaviour of undisturbed completely decomposed granite (CDG) soil, a series of in situ and laboratory direct shear tests were carried out, under different normal stress and moisture contents. The test results showed that the increasing moisture content could obviously weaken the shear strength, cohesion, and frictional angle. Two linear equations were proposed for estimating the cohesion and the frictional angle at any moisture content in the field. The estimated strength parameters could be used for safety evaluation and/or engineering design of CDG cutting slope. The rate of reduction of the cohesion was much higher than that of the tangent value of frictional angle. Due to the disturbance of laboratory sample and size effect, the strength parameters obtained from the in situ test were a little bit higher than those from the laboratory test.